PENETAPAN KADAR FLAVONOID DAN FENOLIK DARI EKSTRAK ETANOL BUAH LEMBA (Molinera latifolia Dryand. Ex W.T. Aiton) SECARA SPEKTROFOTOMETRI UV-VIS - Deswanti, Wina R; D, Sari Dewi (Herbal Medicine Journal, 2024)
The research was carried out by analyzing flavonoid and phenolic levels from ethanol extract samples of lemba fruit. The ethanol extract was prepared using the maceration method. Namely by soaking with 96% ethanol solvent. The extraction results were then analyzed for active ingredient levels, namely flavonoid levels and phenolic levels using UV-Vis spectroscopy. The analysis results showed that the flavonoid content and phenolic content were respectively 120 mg QE/g ethanol extract of lemba fruit and 56 mg GAE/g ethanol extract of lemba fruit.